Monitoring, reporting, and verification system for rice production aligned with Paris Agreement transparency guidelines - Nelson, Katherine; Sander, Björn Ole; Bui Tan Yen; Yadav, Sudhir; Laborte, Alice G. (2022)
This critical review takes a novel approach to assessing the existing Monitoring, Reporting and Verification (MRV) methodology and tools and provides expert-based recommendations for adjusted MRV standards that adapt current guidelines as a promising way forward to deliver transparency in meeting the Nationally Determined Contributions of Vietnam. Additionally, this is a timely proposition given the necessity to define an MRV framework for NAMAs for the rice sector. We are recommending a multi-pronged approach using several tools that can support and validate each other to achieve a robust mechanism for MRV estimations in the rice sector. Examples from the country will be used as a case study given their government’s strong commitment to mitigation in the rice sector.